СПОРТ ТАКОМИЛЛАШУВ БОСҚИЧИДА ГИМНАСТИКАЧИЛАР МАШҒУЛОТ ЖАРАЁНИНИ ТИББИЙ – ФУНКЦИОНАЛ КЎРСАТКИЧЛАРИ АСОСИДА НАЗОРАТ ҚИЛИШ - Умаров, Д.Х. (SCIENCE and SOCIETY, 2021)
The article analyzes the management of loads on the basis of medical and functional indicators, based on the condition of the participants, on the basis of identifying the possibility of a quick effect of physical loads on the body of gymnasts. Also, individual proposals and recommendations for adapting to training were developed.